Subclinical hypothyroidism association with lipid metabolism disturbance and oxidative stress - Mughal, Zaib-Un-Nisa; Zai, Jawaid Ahmed; Gill, Nazia Parveen; Chughtai, Latafat Ali; Khand, Aftab Ahmed; Soomro, Asma (Journal of Liaquat University of Medical & Health Sciences, 2022)
OBJECTIVE: To evaluate the lipid disturbance and oxidative stress in females with subclinical hypothyroidism. METHODOLOGY: This case-control study was conducted at the Department of the Physiology University of Sindh, Jamshoro from April – September 2018. A total of 80 females were selected by random technique and were divided into two groups. Subjects with a history of episodic higher TSH discordant to FT4 levels and current levels of TSH ranging between 4.5mI U/L-<10mI U/L were selected for the study, subjects with hormone replacement therapy, chronic diseases or medication, pregnancy, or smoking habits were excluded. Thyroid profile (TSH, fT4), lipid profile (LDL, HDL, triglyceride, and total cholesterol), oxidative stress markers (MDA, AOPP, ABTS assay, CAT, SOD, GSH, and NO), and C reactive proteins were investigated and compared in subclinically hypo thyroid’s females (SCH) with controls (Cont) females reside in Hyderabad Sindh, Pakistan. SPSS (statistical package for the social sciences) version 20.0 was used for statistical analysis. RESULTS: We observed SCH group subjects with elevated TSH (7.41±0.23) having a slight increase in their LDL (116.39±2.52) and triglyceride levels (122.75±4.74), and also showing elevated MDA (2.49±0.17), AOPP (91.25±1.98) level, but had decreased level of GSH (119.33±2.19). However, no significant difference has been found in CAT, SOD, NO, and C - reactive protein between the two groups. CONCLUSION: Observations of present studies suggestive of disturbed lipid metabolism in subclinically hypothyroid’s females and a burdened antioxidants status. KEYWORDS: Lipid Profile, Thyroid profile, Oxidative Stress markers, Subclinical hypothyroidism, C reactive protein.